Heterogeneity of IGF-1 Levels in Children with hCG-Induced Precocious Puberty - Han Chen; Cai‐Yan Mo; Ling-Yu Zhong; Li -Yong Zhong (International Journal of Endocrinology)
Objective. Sex steroid stimulates growth hormone release during puberty. However, the role of IGF-1 levels in human-chorionic-gonadotropin-induced precocious puberty remains unclear. Methods. A retrospective study reviewing thirty patients with precocious puberty due to human-chorionic-gonadotropin-secreting intracranial germ cell tumors was performed. Changes in IGF-1 levels were collected. Result. All patients included were boys. At diagnosis, the median IGF-1 standard deviation was 0.87 (0.1, 1.87). When human-chorionic-gonadotropin normalized, the median IGF-1 standard deviation was 1.58 (−0.53, 2.55), which is slightly higher than baseline (p=0.408). When patients completed their therapeutic plan, the median IGF-1 standard deviation was 0.10 (−1.05, 0.68), which was significantly lower than that of baseline (p=0.004) and of human-chorionic-gonadotropin being normalized (p=0.003). At the last visit, the mean IGF-1 standard deviation was −1.11(−1.97, 0.76), which is slightly lower than that of baseline (p=0.109) and post-therapy levels (p=0.575), but significantly lower than that of human-chorionic-gonadotropin being normalized. Two patients had IGF-1 levels above 2 standard deviations at diagnosis, eight at the time when human-chorionic-gonadotropin normalized, and two at the end of therapy. Only one patient had an IGF-1 level below 2 standard deviations at diagnosis and at the time when human-chorionic-gonadotropin normalized, and two patients at the end of therapy. At the last follow-up, all patients had normal IGF-1 levels. Conclusion. IGF-1 levels in patients with human-chorionic-gonadotropin-induced precocious puberty have heterogeneity, but IGF-1 standard deviations are mostly within the normal range. If elevated, it might decline later with a decrease in human-chorionic-gonadotropin level. IGF-1 levels seem not valuable enough to assess human-chorionic-gonadotropin-induced precocity regression.